Metakognisi Siswa SMA dalam Menyelesaikan Masalah Matematika - Usman Mulbar; Alimuddin; St. Mukarramah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This research is a descriptive research that aims to describe the metacognition of high school students in solving mathematical problems regarding students' academic abilities. The subjects were students in grade XI on a High School that selected based on certain criteria with snowball sampling technique. The data were collected through problem-solving test which was supported by interview data. Based on the research result, can be concluded that students with high and low academical abilities had an awareness of the facts they had and were aware of how to use a strategy. However, only high-ability students had an awareness of when and why a strategy should be applied. It showed that in solving mathematical problems students with high academical ability involve three aspects of metacognitive knowledge namely declarative knowledge, procedural knowledge, and conditional knowledge nicely, while students with low academical ability only involve two aspects of metacognitive knowledge i.edeclarative knowledge and procedural knowledge.